2017
DOI: 10.1016/j.ypmed.2017.06.025
|View full text |Cite|
|
Sign up to set email alerts
|

Cigarette smoking risk-reducing beliefs: Findings from the United States Health Information National Trends Survey

Abstract: Cigarette smoking risk-reducing beliefs are ideas that certain health promoting behaviors (e.g., exercise) may mitigate the risks associated with smoking. The objective of this study was to describe smoking risk-reducing beliefs and the belief that quitting can reduce the harmful effects of smoking among the U.S. adult population and the associations between these beliefs, current smoking status, and sociodemographics. Data were from the Health Information National Trends Survey 4 (HINTS 4) Cycles 3 and 4 (201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Quit confidence was measured using a single item: 29 ‘How confident are you that you could quit smoking for good if you wanted to?’. The response options were on a scale of 1–5 where 1=‘not at all’ and 5=‘extremely’.…”
Section: Methodsmentioning
confidence: 99%
“…Quit confidence was measured using a single item: 29 ‘How confident are you that you could quit smoking for good if you wanted to?’. The response options were on a scale of 1–5 where 1=‘not at all’ and 5=‘extremely’.…”
Section: Methodsmentioning
confidence: 99%
“… 23 The majority of the smokers believed that quitting tobacco smoking would help them reduce its detrimental effects. 24 Health problems, either for oneself or for a close relation, were found to be one of the major motivations for smoking cessation. 25 Studies have also reported that the individuals who attempted to quit smoking after the diagnosis of CVD gradually restarted after certain period.…”
Section: Discussionmentioning
confidence: 99%
“…The sampling design and methodology have been described previously. 14 There have been 12 iterations of HINTS; this study analyzes HINTS 5, Cycle 2, the most recent administration and the first version to include questions on palliative care knowledge and information sourcing. Respondents were asked about their knowledge of PC, and those who indicated they were knowledgeable about it were asked additional follow-up questions to assess their beliefs on the meaning of palliative care, as well as their primary sources of information on the topic.…”
Section: Methodsmentioning
confidence: 99%